CULTURAL NON-EQUIVALENCE IN TRANSLATING HAMKA’S DI BAWAH LINDUNGAN KAʿBAH: AN ANALYSIS OF MEANING AND CROSS-CULTURAL CONTEXTS - Uki Sukiman; Azhar Ismail Hasibuan; Azhari (ALLAIS Journal of Arabic Language and Literature, 2026)
This study demonstrates that the primary challenge in translating Indonesian literary works into Arabic lies in the cultural elements embedded in metaphors, proverbs, and local expressions. Employing a qualitative textual analysis of Hamka’s Di Bawah Lindungan Kaʿbah, the research reveals that differences in worldview between Indonesian and Arab societies influence lexical choices and stylistic expressions, making literal translation insufficient. The findings highlight the necessity for translators to grasp the cultural context of the source text to ensure comprehensive meaning transfer. The study contributes to translation studies by formulating strategies that integrate semantic and stylistic approaches, including transliteration with explanatory notes, functional equivalence in the target culture, and the preservation of social metaphors. These strategies prove effective in maintaining cultural authenticity while ensuring readability for Arabic audiences. Overall, the research reinforces the view that literary translation is an act of intercultural mediation, synthesizing linguistic, semantic, and cultural dimensions to preserve meaning, aesthetic nuance, and cultural resonance in the target language.